Catechins, theaflavins and ginger freeze-dried extract based functional drink significantly mitigate the hepatic, diabetic and lipid abnormalities in rat model - Kashif, Muhammad; Imran, Ali; Saeed, Farhan; Chatha, Shahzad Ali Shahid; Arshad, Muhammad Umair (Cellular and Molecular Biology, 2021)
The Current study was planned to explore the therapeutic potential of green tea, black tea and ginger based nutraceuticals (catechins, theaflavins and ginger freeze dried extract) against obesity, diabetes and renal malfunctioning. Bioevaluation study was carried out by involving 250 male Sprague Dawley rats. Accordingly, three types of studies were conducted on the basis of different diets i.e. study I (Hyperglycemic rats), study II (obese rats), study III (liver malfunctional rats) each study comprised of five groups of rats ten in each (Sample size according to power analysis) were provided the five types of drinks i.e. control, theaflavin enriched, catechins enriched, ginger extract supplemented and combination of catechins, theaflavins and ginger extract were given to the representative groups. Results showed that the body weight of rats effected significantly with functional drinks in all studies. However, catechin enriched drink (T1) resulted maximum reduction in weight during the entire study. Similarly, T2 exerted maximum decline in cholesterol level during study I, II and III by 11.03 & 10.63, 7.62 & 8.05 and 5.99 & 6.01% whereas LDL by 14.25 & 15.10, 10.45 & 12.10 and 7.25 & 8.01%, respectively (trial 1 & 2). The attenuation in serum glucose and enhancement in insulin level of rats are the indicators for the positive impact of black tea functional drinks. In this context, Catechins+theaflavins+GFD enriched drink (T4) Showed better performance than rest and caused 8.82 & 9.77, 11.03 & 12.23 and 5.83 & 5.96% reduction in glucose. Moreover, the T4 significantly improved the liver and antioxidant enzymes. Accordingly, T4 was proved effective for glutathione enhancement whilst T2 alleviated TBARS efficiently during the investigation. The normal ranges of renal function tests and hematological aspects proved the safety of resultant drinks. From the current exploration, it is concluded that drinks supplemented with theaflavin and catechins & GFD are effectual to mitigate lifestyle related malfunctioning.